Role and Determinants of Adherence to Off-loading in Diabetic Foot Ulcer Healing: A Prospective Investigation - Crews, Ryan T. (Diabetes Care, 2016)
OBJECTIVE: Studies indicate that off-loading adherence is low in patients with diabetic foot ulcers (DFUs), which may subsequently delay healing. However, there is little empirical evidence for this relationship or the factors that influence adherence. RESEARCH DESIGN AND METHODS: This prospective, multicenter, international study of 79 (46 from the U.K. and 33 the U.S.) persons with type 2 diabetes and plantar DFUs assessed the association between off-loading adherence and DFU healing over a 6-week period. Additionally, potential demographic, disease, and psychological determinants of adherence were examined. DFUs were off-loaded with a removable device (77% a removable cast walker). Off-loading adherence was assessed objectively by activity monitors. Patient-reported measures included Hospital Anxiety and Depression Scale (HADS), Neuropathy and Foot Ulcer Quality of Life (NeuroQoL) instrument, and Revised Illness Perception Questionnaire (IPQ-R). RESULTS: Off-loading adherence was monitored for 35 ± 10 days, and devices were used during 59 ± 22% of subjects' activity. In multivariate analyses, smaller baseline DFU size, U.K. study site, and better off-loading adherence predicted smaller DFU size at 6 weeks (P < 0.05). Better off-loading adherence was, in turn, predicted by larger and more severe baseline DFUs, more severe neuropathy, and NeuroQoL foot pain (P < 0.05). In contrast, greater NeuroQoL postural instability predicted worse off-loading adherence (P < 0.001). HADS and IPQ-R measures were not significantly associated with off-loading adherence. CONCLUSIONS: Off-loading adherence is associated with the amount of DFU healing that occurs, while postural instability is a powerful predictor of nonadherence. Clinicians should take this neuropathic symptom into consideration when selecting an off-loading device, as off-loading–induced postural instability may further contribute to nonadherence.